The Effect of Technological Advances in ManyOption Applications on User Satisfaction in Environmental Dues Management which Impacts User Loyalty at Gandaria Icon City Apartments - Evi Agustina Br Dongoran; Bertalya Bertalya (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2022)
The development of information technology is currently growing rapidly so that people are getting smarter and want the efficiency of time and energy in carrying out all their activities. This is in line with the development of social commerce by increasing it through e-commerce. E-commerce was previously unthinkable that it would really help humans, in fact, it has become an information technology that is currently a major need. Information technology that is created and then helps humans in all their affairs. Information technology is commonly known as information system applications. Information system applications can be the answer to improve performance through data processing that is accurate, fast, precise, and saves time so that it supports daily operations starting from the payment of monthly dues. This study will use the intervening path analysis method implemented in the SmartPLS 3.0 calculation tool. The study was conducted using 100 data samples and the results of the path coefficient test for the relationship between the application technology progress variable and user loyalty with user satisfaction, the path coefficient parameter coefficient value was 0.352 and the t-statistic value was 6,094 <1.96 at a significant level ???? = 0.05 with p-value. 0.000> 0.05 so it can be concluded that user satisfaction has a positive and significant effect in influencing the relationship between application technology progress and user loyalty.